Application Of Jean Nursing Model Theory In Hypertensive Patients With The Application Of Finger Hold Relaxation Techniques At The Outpatient Poly Of Rupit Hospital, North Musi Rawas Regency In 2022 - Fatmawati, Fatmawati; Murwati, Murwati; Sofais, Danur Azissah roeslina (Student Scientific Journal, 2023)
Intoduction: Hypertension is a systemic blood pressure in which systolic pressure>140 mmHg and dystolic >90 mmHg. High blood pressure or hypertension is a medical condition in which there is a chronic increase in blood pressure (over a long period of time). People who have at least three blood pressure readings that exceed 140/90 mmHg at rest are thought to have high blood conditions. Always high blood pressure is one of the risk factors for stroke, heart attack, heart failure and arterial aneurysm, and is a major cause of chronic heart failure.This finger-gripping technique comes from an ancient healing practice that originated in Japan known as Jin Shin Jyutsu. Master Jiro Murai was a Japanese healer and philosopher who rediscovered the ancient healing practice of Jin Shin Jyutsu in the early 20th century. A practitioner of Jin Shin Jyutsu uses both hands to hold the combination (SEL). There are about 26 SEL (Safety Energy Locks) points along the energy pathway. As pathways become obstructed, energy becomes stagnant. This initially affects areas of stagnation but has the potential to create imbalances along the entire path.In this study, the method used is to use a method, namely a nursing process approach based on the chosen nursing theory, the techniques used in data collection, namely by interview, observation, physical examination and conducting nursing care. Data sources obtained or used are primary obtained directly from patients and secondary data obtained from family, health workers and documentation from other examination results to carry out nursing care, while literature study is studying source books related to nursing care given to patients. The main purpose of nursing using Jean Watson's theory by using finger grip techniques in hypertensive patients by implementing evidance-based practice in nursing practice is to improve the quality of care and provide the best results from the nursing care provided. In addition, with the maximization of the quality of care, the patient's recovery rate can be faster and the length of treatment can be shorter and the cost of treatment can be reduced.